2009
DOI: 10.1007/s00228-009-0660-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pharmacogenetics on indinavir disposition and short-term response in HIV patients initiating HAART

Abstract: The CYP3A4*1B polymorphism was found to influence the pharmacokinetics of indinavir and, to some extent, the biochemical safety of indinavir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 50 publications
1
18
1
2
Order By: Relevance
“…(51,52). It is uncertain whether interindividual differences in drug metabolism can be attributed to the allelic variant CYP3A4*1B (47,49,(53)(54)(55)(56)(57)(58); it has also been suggested that a linkage disequilibrium between CYP3A4*1B and CYP3A5*1A (and thus increased CYP3A5 expression) could be the actual cause of the altered metabolism (47,58,59). No effect of CYP3A5*3 could be detected in our study.…”
Section: Discussioncontrasting
confidence: 44%
“…(51,52). It is uncertain whether interindividual differences in drug metabolism can be attributed to the allelic variant CYP3A4*1B (47,49,(53)(54)(55)(56)(57)(58); it has also been suggested that a linkage disequilibrium between CYP3A4*1B and CYP3A5*1A (and thus increased CYP3A5 expression) could be the actual cause of the altered metabolism (47,58,59). No effect of CYP3A5*3 could be detected in our study.…”
Section: Discussioncontrasting
confidence: 44%
“…Patients received a combination of two NRTIs plus one PI as antiretroviral therapy. Population PK analyses of the data from the nelfinavir group and the ritonavir-boosted indinavir group obtained in this trial were performed to evaluate the impact of genetic polymorphisms on nelfinavir and indinavir pharmaco-kinetics (PK) and the link between concentrations and shortterm efficacy (10,21). A substudy of the COPHAR2-ANRS111 trial consisted of measuring plasma and intracellular concentrations of AZT and 3TC in patients whose treatment contained AZT and 3TC as NRTIs with a PI.…”
mentioning
confidence: 99%
“…The functional significance of CYP3A4*1B mutation has recently been reported. CYP3A4*1B/ CYP3A4*1B genotype has been reported to reduce the absorption of indinavir in patients initiating Highly Active Anti-Retroviral Treatment (HAART) naïve patients [14]. This SNP has also been associated with the more aggressive forms and advanced clinical stages of prostate cancer in African-Americans but not in Portugese victims [31].…”
Section: Discussionmentioning
confidence: 99%
“…Substrates of CYP3A4 include methadone, anti-depressants, immunosuppressive agents, macrolide antibiotics, benzodiazepines, calcium channel blockers [12], and several antiretroviral [4,13,14] used in HIV/AIDS. Also importantly, CYP3A4 is involved in the metabolism of endogenous substances that include testosterone [15], progesterone [16], cortisol [17], and 17β-estradiol [18], and this may be important in the patho physiology of diseases including drug dependence.…”
Section: Introductionmentioning
confidence: 99%